Sustainability Reporting in the University Context—A Review and Analysis of the Literature - Abello-Romero, J (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
This paper aims to determine the key themes addressed in sustainability reporting in higher education institutions (HEIs), focusing on papers indexed in the Scopus database until October 2024. The number of papers selected was fewer than the number of articles addressing sustainability reporting in corporate settings. We present the findings of this search by providing some metrics and an analysis of the selected texts through the construction of ten categories and 26 subcategories. Our study differs from previous works by providing an analysis of the content of some of the reviewed articles. © 2024 by the authors.